2008
DOI: 10.1152/ajprenal.00142.2007
|View full text |Cite
|
Sign up to set email alerts
|

MKL1 mediates TGF-β1-induced α-smooth muscle actin expression in human renal epithelial cells

Abstract: Elberg G, Chen L, Elberg D, Chan MD, Logan CJ, Turman MA. MKL1 mediates TGF-␤1-induced ␣-smooth muscle actin expression in human renal epithelial cells. Am J Physiol Renal Physiol 294: F1116-F1128, 2008. First published March 12, 2008 doi:10.1152/ajprenal.00142.2007.-Transforming growth factor-␤1 (TGF-␤1) is known to induce epithelial-mesenchymal transition in the kidney, a process involved in tubulointerstitial fibrosis. We hypothesized that a coactivator of the serum response factor (SRF), megakaryoblastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 76 publications
(109 reference statements)
3
84
0
Order By: Relevance
“…Levels of MRTF-A were significantly higher in isoxazole-treated fibroblasts, which led to a greater proportion of cells displaying nuclear accumulation of MRTF-A. A previous study reported regulation of MRTF-A protein stability by the proteasome degradation pathway, suggesting the possibility that isoxazole might inhibit the ubiquitin-proteasome system (19).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Levels of MRTF-A were significantly higher in isoxazole-treated fibroblasts, which led to a greater proportion of cells displaying nuclear accumulation of MRTF-A. A previous study reported regulation of MRTF-A protein stability by the proteasome degradation pathway, suggesting the possibility that isoxazole might inhibit the ubiquitin-proteasome system (19).…”
Section: Discussionmentioning
confidence: 77%
“…Situations of stress that locally alter actin dynamics and promote F-actin polymerization promote nuclear accumulation of MRTFs (18)(19)(20)(21)(22)(23)(24). SRF/MRTF complexes bind to consensus CArG elements [CC(A/T) 6 GG] within the promoters of contractile and SMC-specific target genes, most notably smooth muscle α-actin (SMA, ACTA2) and transgelin (TAGLN, SM22) (25).…”
mentioning
confidence: 99%
“…G-actin binds to the RPEL motifs on MRTF-A and, when bound, G-actin has been proposed to inhibit nuclear import, enhance nuclear export, and repress transcription of MRTF-A target genes (56). Thus far, work in proximal tubular epithelial cells has been pivotal in determining the involvement of MRTF-A subcellular localization in the context of TGFβ-induced EMT (34,37,57). Morita et al (2007) demonstrated that the presence of constitutively active MRTF-A was sufficient to induce expression of αSMA, in contrast to dominant negative MRTF-A, the pathophysiology of fibrosis of the lens and other tissues.…”
Section: Mrtf-a Is a Downstream Target Of Rhoa/rock Signaling In Rat mentioning
confidence: 99%
“…Also, approximately 40% of MKL1 null mice embryos suffered from lethal cardiac cell necrosis with mitochondrial dysfunction (Parmacek, 2007). In addition, it has been reported that the expression of MKL1 in the smooth muscle cells may be associated with RhoA and TGF-beta-dependent channels, and that these two channels have an important role in the process of atherosclerosis (Elberg et al, 2008). Hence, we hypothesized that MKL1 may also play an important role in coronary atherosclerosis.…”
Section: Discussionmentioning
confidence: 96%
“…Human MKL1 gene is located on chromosome 22q13 (Ma et al, 2001). According to reports, MKL1 may have effects on the formation of the cardiovascular system and maintenance processes (Cen et al., 2004) through the regulation of abnormal proliferation of smooth muscle cells (Sata et al, 2002;Selvaraj and Prywes, 2003;Du et al, 2004;Parmacek, 2007;Kihara et al, 2008), as well as through RhoA and TGF-beta-dependent channels (Elberg et al, 2008) participating in coronary heart disease and its development. Hinohara et al (2009) first discovered the -184C> T polymorphism of MKL1 involved in the pathogenesis of coronary heart disease of Japanese and Koreans.…”
Section: Introductionmentioning
confidence: 99%